Hyperglycemia and PPARγ Antagonistically Influence Macrophage Polarization and Infarct Healing After Ischemic Stroke. Issue 10 (October 2015) - Gliem, Michael; Klotz, Luisa; van Rooijen, Nico; Hartung, Hans-Peter; Jander, Sebastian
<x xml:space="preserve">Abstract</x> Background and Purpose— Secondary intracerebral hemorrhage (sICH) is a potentially serious complication of ischemic stroke, in particular under concomitant oral anticoagulation. Previous studies in murine stroke models defined a novel vascular repair function of hematogenous monocytes/macrophages (MO/MP), which proved essential for the prevention of oral anticoagulation–associated sICH. Here, we addressed the question whether hyperglycemia as a clinically relevant prohemorrhagic risk factor and peroxisome proliferator-activated receptor gamma (PPARγ) activation affect MO/MP differentiation and the risk of sICH after ischemic stroke. Methods— Oral anticoagulation–associated sICH was induced by phenprocoumon feeding to mice undergoing transient middle cerebral artery occlusion. Hyperglycemia was induced by streptozotocin treatment. The role of PPARγ-dependent MO/MP differentiation was addressed in mice with myeloid cell–specific PPARγ-knockout (LysM-PPARγ(KO)). Pharmacological PPARγ activation via pioglitazone was tested as a treatment option. Results— Hyperglycemic mice and normoglycemic LysM-PPARγ(KO) mice exhibited abnormal proinflammatory skewing of their hematogenous MO/MP response and abnormal vascular remodeling in the infarct border zone, leading to an increased rate of oral anticoagulation–associated sICH. Pharmacological PPARγ activation in hyperglycemic mice corrected the inflammatory response toward an anti-inflammatory profile, stabilized neovessels in the infarct border zone, and reduced the rate of sICH. This preventive effect was dependent on the presence of macrophages, but independent from effects on blood glucose levels. Conclusions— Hyperglycemia and macrophage-specific PPARγ activation exert opposing effects on MO/MP polarization in ischemic stroke lesions and, thereby, critically determine the risk of hemorrhagic infarct transformation.